Non-surgical Treatment of Condylar Fracture in an 11-Year-Old Patient: a Case Report - Angela Pia Cazzolla; Graziano Montaruli; Nunzio Francesco Testa; Gianfranco Favia; Maria Grazia Lacaita; Lorenzo Lo Muzio; Domenico Ciavarella (Stilus Optimus, 2018)
Background: Mandibular condylar fractures commonly occur after trauma and account for 25 to 35% of all mandibular fractures; its appropriate therapy still remains a point of controversy in children. The purpose of this paper is to describe the treatment of an 11-years-old male patient affected by neck-condylar fracture as result of trauma in evolutive age. Methods: No surgical treatment was performed. A functional therapy was applied with a jaw splint. A closed treatment for mandibular condyle fractures was preferred because the amount of condylar displacement wasn't considerable. Results: The early treatment with functional therapy generated a functional adaptation of the condyle in the glenoid fossa and a normal mandibular function. After a 12-month follow-up the fracture resolution and an optimal condylar position were recorded. Conclusions: The current case report and literature review showed that non-surgical therapy of neck-condylar fracture in a child with lower resin splint can restore mandibular movements and aesthetics. Facial growth after one year treatment resulted normal. A conservative treatment may be appropriate for children in selected cases with minimally displaced condyle.